Pemahaman Masyarakat terhadap Kesehatan Lingkungan dengan Menggunakan Pendekatan Asuhan Keperawatan Komunitas - Maghfirah Hariyanti Syamsul Bahri; Andi Agustang; Nurlita Pertiwi; Muhasidah Muhasidah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to describe the understanding of the residents of Dusun Diccekang, Moncongloe Village, Maros on environmental health by using the Community Nursing Care approach. The method used is descriptive quantitative. The sampling technique was carried out by purposive random sampling. The results showed that there are still Dusun Dicekang residents who throw garbage (24%) and wastewater (32%) carelessly, water reservoirs at home contain larvae (40%) and as many as 36% of households still lack knowledge. In conclusion, the understanding of the residents of Diccekang Hamlet, Moncongloe Maros Village is quite good, but there are still some residents who have a poor understanding of environmental health. Keywords: Community Nursing, Environmental Health